SEJARAH, KURIKULUM, DAN BAHASA INDONESIA DI JURUSAN INTERPRETASI DAN TERJEMAHAN BAHASA MELAYU-INDONESIA (ITBMI), HANKUK UNIVERSITY OF FOREIGN STUDIES, KAMPUS GLOBAL, KOREA SELATAN - Kim Jang Gyem (Universitas Andalas, 2019)
Indonesian language is a language that has an important role both within Indonesia and internationally, particularly in Asia. Therefore, the teaching of Indonesian overseas are growing and developing. The focus of this article is teaching Bahasa Indonesia at the Hankuk University of Foreign Studies (HUFS), South Korea was established in 1954 and the Department of MalayIndonesia (BMI), began in 1964 (Imun Campus) and 1982 (Global Campus). The programs are held at both HUFS campus locations, the Global Campus and Imun Campus with the same system and curriculum. At the later stage, with the development and dynamics of academic, Global Campus is reformed into Department of Interpretation and Translation Malay-Indonesia (DMIT), which is characterized by changes in course and curriculum system, particularly in the addition of courses on the interpretation/translation. In addition, changes were also made to other types of courses, number of credit hours of courses and distribution of courses. This is conducted in order to continue to improve the quality of learning that will ultimately produce high quality graduates. The change is implemented by considering the continuity of the working world, advice from faculty discussions with students, and analyzes the results of the questionnaire. Keyword: DMIT, ITBMI, HUFS Campus Global, Come to HUFS, meet the world!